Analysing the Validity of Misconceptions about Open and Distance Learning among High school teachers in Mashonaland Central Province of Zimbabwe - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2017)
This study identifies a set of misconceptions about distance education among high schoolteachers in Mashonaland Central of Zimbabwe. These misconceptions were verifiedquantitatively with 60 systematic randomly selected high school teachers who guide students ontertiary enrolment selection. Data were collected using questionnaire and interview and analysedusing simple percentages and content analysis. The findings showed that the misconceptionswhich had higher ranking values among the respondents were: ODL is an opportunistic form oflearning for average or less intelligent students (60 or 100%); ODL as a mode of learning withlow quality assurance (58 or 96.7%); ODL as inferior form of learning since it is technologymediated(56 or 93.3%) and less vigorous in comparison with the conventional mode of learning(56 or 93.3%). The study recommended, among others, that marketing and workshops should beorganized for high school teachers, and high school students on the importance of distancelearning at tertiary level.